Study on the Dynamic Deformation of Road High Liquid Limit Subgrade Soil - Zheng Lu; Ran Fang; Yongxiang Zhan; Hailin Yao (Advances in Civil Engineering)
In order to evaluate the traffic-load-induced cumulative deformation of road high liquid limit subgrade soil, a series of laboratory tests are performed to determine the physical and mechanical properties of high liquid limit soil. A cumulative deformation model is then developed with consideration of the effects of dynamic deviator stress, the number of repeated loadings, and the material properties of subgrade soil. Based on Lu’s vehicle-road-ground coupling model, the traffic-load-induced stress, which is very important in predicting cumulative settlement of the subgrade, is calculated explicitly. The layerwise summation method is used to evaluate the traffic-load-induced cumulative deformation. Moreover, a parametric study is conducted using numerical computation and the results show that the traffic-load-induced cumulative deformation is mainly generated from the shallow soil, and the additional dynamic load plays an important role in analyzing the traffic-load-induced settlement.